IMPLIKASI KEBIJAKAN PENGAKATAN SEKRETARIS DESA MENJADI PEGAWAI NEGERI SIPIL BERDASARKAN PP NO. 45 TAHUN 2007 DI KECAMATAN WIRADESA KABUPATEN PEKALONGAN - Sri Pujiningsih; Ichsan Syuhudi; Siti Zulaekha (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2012)
Policies village government secretary to the government employees regulated in Act Number  32  Year  2004  on  Regional  Government  which  in  turn  followed  by  the issuance of Government Regulation No. 45 Year 2007 regarding appointment of the Secretary  of  the  Village  government  being  government  employees.  Appointment  of secretary  of  the  village  government  into  the  government  employees  be  automatic without passing Candidate government employees.The policy is the policy on the one hand  is  a  must,  as  already  mandated  by  the  Act,  but  on  the  other  hand  the implementation implications for the organization of the village government. One was in the form of demands from government officials that the village of the government employees  appointments  are not  just  for the  village government secretary  only, but also followed the appointment of village government officials.